2003
DOI: 10.1016/s0043-1354(03)00440-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of free chlorine on Burkholderia pseudomallei in potable water

Abstract: Chlorine is widely used in public water supplies to provide a disinfection barrier. The effect of chlorine disinfection on the water-borne pathogen Burkholderia pseudomallei was assessed using multiple techniques. After exposure to chlorine viable bacteria were undetectable by conventional plate count techniques, however persistence of B. pseudomallei was verified by flow cytometry and bacteria were recoverable following a simple one step broth procedure. The minimum residual chlorine concentration and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…This is in agreement with the findings of Kim et al (2002) who showed that, in general, oxidising disinfectants (chlorine and monochloramine in this study) were more effective than non-oxidising ones against Legionella in water systems. The reduction by chlorine calculated by MPN in this study is greater than those estimates produced by flow cytometry (Howard and Inglis, 2003a), however flow cytometry was not used due to the lower detection limit of 10 4 CFU/mL.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…This is in agreement with the findings of Kim et al (2002) who showed that, in general, oxidising disinfectants (chlorine and monochloramine in this study) were more effective than non-oxidising ones against Legionella in water systems. The reduction by chlorine calculated by MPN in this study is greater than those estimates produced by flow cytometry (Howard and Inglis, 2003a), however flow cytometry was not used due to the lower detection limit of 10 4 CFU/mL.…”
Section: Discussionmentioning
confidence: 53%
“…Survival of groups of chlorine "tolerant", chlorine "sensitive" and mucoid strains from the earlier study (Howard and Inglis, 2003a) showed a difference between the three disinfecting agents used in this study. When exposed to chlorine the mucoid strains were as resistant to chlorine as the tolerant group.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations